Drug-resistant hypertension in primary aldosteronism patients undergoing adrenal vein sampling: the AVIS-2-RH study - Rossi, Gian Paolo; Rossitto, Giacomo; Amar, Laurence; Azizi, Michel; Riester, Anna; Reincke, Martin; Degenhart, Christoph; Widimsky, Jiri; Naruse, Mitsuhide; Deinum, Jaap; Schultze Kool, Leo; Kocjan, Tomaz; et al. (European journal of preventive cardiology, 2022)
AIMS: We aimed at determining the rate of drug-resistant arterial hypertension in patients with an unambiguous diagnosis of primary aldosteronism (PA). Moreover, we sought for investigating the diagnostic performance of adrenal vein sampling (AVS), and the effect of adrenalectomy on blood pressure (BP) and prior treatment resistance in PA patients subtyped by AVS in major referral centres. METHODS AND RESULTS: The Adrenal Vein Sampling International Study-2 (AVIS-2) was a multicentre international study that recruited consecutive PA patients submitted to AVS, according to current guidelines, during 15 years. The patients were over 18 years old with arterial hypertension and had an unambiguous diagnosis of PA. The rate of resistant hypertension was assessed at baseline and after adrenalectomy using the American Heart Association (AHA) 2018 definition. Information on presence or absence of resistant hypertension was available in 89% of the 1625 enrolled PA patients. Based on the AHA 2018 criteria, resistant hypertension was found in 20% of patients, of which about two-thirds (14%) were men and one-third (6%) women (χ2 = 17.1, P < 1*10-4) with a higher rate of RH in men than in women (23% vs. 15% P < 1*10-4). Of the 292 patients with resistant hypertension, 98 (34%) underwent unilateral AVS-guided adrenalectomy, which resolved BP resistance to antihypertensive treatment in all. CONCLUSIONS: (i) Resistant hypertension is a common presentation in patients seeking surgical cure of PA; (ii) AVS is key for the optimal management of patients with PA due to resistant hypertension; and (iii) AVS-guided adrenalectomy allowed resolution of treatment-resistant hypertension.
Keywords: Primary aldosteronism; hypertenze; Female; Drug-resistant hypertension; ženské pohlaví; adrenalektomie; Adolescent; lidé; Adrenal vein sampling; nadledviny; Adrenalectomy; retrospektivní studie; Hyperaldosteronism; Hypertension; Male; Aldosterone; Adrenal Glands; mužské pohlaví; hyperaldosteronismus; Retrospective Studies; mladiství; Humans